Pengaruh Jenis dan Dosis Pupuk Kandang yang Berbeda terhadap Pertumbuhan dan Hasil Tomat Kultivar TM Blazer - Wisnu nur rahmat, Gandara; Mutakin, Jenal; Sativa, Novriza (Universitas Garut, 2025)
Tomato (Solanum lycopersicum) is a widely consumed vegetable crop. Proper cultivation techniques, particularly fertilization, play a crucial role in enhancing its productivity. The application of various types and doses of organic fertilizers is expected to influence the growth and yield of the TM Blazer tomato cultivar. However, organic fertilizer application may also lead to an increase in weed growth in the field, necessitating an assessment of weed diversity. This study was conducted from June to September 2024 in Karamatwangi Village, Cisurupan District, Garut Regency. A factorial randomized complete block design (RCBD) with a 4 × 3 factorial arrangement and two replications was employed. The first factor was the type of organic fertilizer (P): p0 (control), p1 (cattle manure), p2 (sheep manure), and p3 (chicken manure). The second factor was the fertilizer dosage (D): d1 (5 tons/ha), d2 (10 tons/ha), and d3 (15 tons/ha). The results indicated no significant interaction between the type and dosage of organic fertilizers. However, chicken manure (p3) exhibited a significant independent effect on plant growth parameters. A dosage of 15 tons/ha significantly influenced plant height, leaf number, stem diameter, leaf area, and fruit weight at 42 and 63 days after transplanting (DAT).